Analisis Biaya dan Pendapatan pada LKMA Pincuran Bonjo Kecamatan Payakumbuh Timur Kota Payakumbuh - Imelfina Musthafa; Siska Fitrianti; Raeza Firsta Wisra (Politeknik Pertanian Negeri Payakumbuh, 2020)
People need funding for helping their business to run well. Nowadays, people tend to avoid make loan to the bank as they have to fulfill many requirements needed for administration. Indonesian government facilitates this problem through Agribusiness Micro Finance Institution (LKMA) to help family sector to access credit for funding. This study was aimed to analyze cost and revenue of LKMA Pincuran Bonjoand to know the feasibility of LKMA Pincuran Bonjo business. This study used analytic descriptive method using case study in LKMA Pincuran Bonjo. This LKMA was chosen for the level of member activeness and the asset growth. The data were collected using unstructured interview and document study on income statement during 2016 to 2018. The study suggested that the total cost is Rp. 81.117.842, Rp. 93.077.138, and Rp.75.105.911, in a row. Salary contributed the most for this cost. While, the total revenue in a row is as follow: Rp.110.833.474, Rp.128.888.559,-, and Rp. 99.521.940, in which the highest revenue was achieved from the loan services. And the benefit achieved during those years was Rp. 29.715.632, Rp. 35.811.421, dan Rp. 24.416.029,. The R/C ratio was 1.37, 1.38 and 1.33, this indicates that LKMA Pincuran Bonjo business is liable to keep running and growing.